2019
DOI: 10.1155/2019/9014698
|View full text |Cite
|
Sign up to set email alerts
|

Association and Interaction Analysis of Lipid Accumulation Product with Impaired Fasting Glucose Risk: A Cross-Sectional Survey

Abstract: Aims Lipid accumulation product (LAP) is put forward as a powerful marker showing the accumulation of visceral fat. The present study is aimed at (i) analyzing the predictive performances of LAP in the identification of impaired fasting glucose (IFG) in Chinese population and (ii) exploring the potentially interactive effect between LAP and other factors on IFG risk. Methods Analysis was conducted on the data obtained from a community-based cross-sectional survey in Chinese population, and all the participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 71 publications
0
11
2
Order By: Relevance
“…However, no signi cant interaction between LAP and general obesity was observed in study population. Previous studies have explored the interaction effect between LAP and abdominal obesity on risk of diabetes [48,55], but our result seem to be inconsistent.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…However, no signi cant interaction between LAP and general obesity was observed in study population. Previous studies have explored the interaction effect between LAP and abdominal obesity on risk of diabetes [48,55], but our result seem to be inconsistent.…”
Section: Discussioncontrasting
confidence: 70%
“…The prevalence of IFG and diabetes gradually increased across LAP quartiles, the values in the fourth quartile of LAP were dramatically higher than in the rst quartile (12.6% vs. 5.9%, 20.8% vs. 8.9%, respectively), and this conclusion was consistent with other similar studies in China. A cross-sectional study in Beijing showed that an elevated level of LAP was closely linked to an increased risk of diabetes in elderly people [47], and a survey in Anhui province con rmed that there is a positive correlation between LAP and IFG [48].…”
Section: Discussionmentioning
confidence: 99%
“…LAP presented as a surrogate marker of visceral adiposity, was reportedly a powerful predictor of prediabetes and CKD, respectively. 9 , 16 , 17 A prospective study in Europe enrolled 148 women with polycystic ovary syndrome proved that elevated LAP was associated with prediabetes. 18 Another community-based cross-sectional survey involving 1777 Chinese participants indicated that LAP showed a better performance in discriminating IFG risk than BMI.…”
Section: Discussionmentioning
confidence: 99%
“…LAP is calculated from WC and fasting TG levels, which has a theoretical basis in reflecting the accumulation of visceral fat [ 19 ]. Several studies indicated that LAP displayed a better predictive ability in metabolic syndrome, diabetes, and impaired fasting glucose as compared with common obesity indices [ 20 – 22 ]. But some studies indicated that high LAP was not associated with an increased risk of T2DM [ 41 ], and LAP may not be an inexpensive tool for predicting T2DM [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second is lipid accumulation product (LAP), calculated from WC and fasting TG levels, which was first proposed to recognize cardiovascular risk in 2005 [ 19 ]. Several studies indicated that LAP displayed a better predictive ability in metabolic syndrome, diabetes, and impaired fasting glucose as compared with common obesity indices [ 20 – 22 ]. Many studies have indicated that metabolic syndrome and its components were risk factors for T2DM [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%